Chemical, physical and mechanical properties on production of medieval paper and cardbord by using grass: article - Nik Mohd Yajid, Nik mahirah; Tan, Huey Ling (2019)
Grass has potential to be developed as paper and cardboard production because they have the lignocellulosic content that almost same as tree, which is main sources for paper production all over the years. The process for paper and card board production was adapted from paper production industry. For this production, grass was cut into very small size to make it easily boiled, then the grass was blend until it soft as pulp. Lastly, the pulp was mold into paper and cardboard using suitable molder and dried under sunlight. The paper sample was analyzed using SEM to show the paper structure, FTIR to analyzed lignocellulosic content and tensile to know the paper strength. Based on result of this study, the thickness of paper and cardboard was 0.1 and 0.5 cm respectively, the moisture removal exceed 90% after left 24 hours in 110o C oven, under SEM magnification, untreated pulp has more impurities, rigid and strong bonds whereas treated pulp have ruptured surface due to lignin removal. For FTIR analysis, the result shows presence of cellulose, hemicellulose and lignin for untreated grass and for treated pulp, only cellulose was presented. The tensile strength for paper and cardboard were 70 N and 63 N respectively. The objectives of this study were achieved since the paper produced from grass have almost same characteristic as paper produced from wood